2015
DOI: 10.1159/000398790
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Caraway Oil Poultices in Treating Irritable Bowel Syndrome - A Randomized Controlled Cross-Over Trial

Abstract: Background/Aim: Irritable bowel syndrome (IBS) is a frequent gastrointestinal disorder, with only limited evidence regarding self-management approaches. This study tested the efficacy of caraway oil poultices (CarO) for treating IBS. Methods: This randomized controlled open-label cross-over trial included three treatment periods with hot CarO and hot olive oil poultice (OlivH) or nonheated poultices (OlivC) with olive oil as control interventions. Patients applied each intervention daily for 3 weeks. The prima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 43 publications
(36 reference statements)
0
5
0
3
Order By: Relevance
“…A group difference of 83 points on the IBS‐SSS total score has been shown to represent a considerable self‐reported improvement . Assuming a standard deviation of 103.8, based on a former trial with IBS patients, a two‐sided, level 5% t test requires a total of 26 patients per study group in order to detect a respective group difference with a statistical power of 80%. To account for the potential loss of statistical power from the withdrawal of up to 10% of participants, the trial aimed to recruit a total of at least 58 patients.…”
Section: Methodsmentioning
confidence: 99%
“…A group difference of 83 points on the IBS‐SSS total score has been shown to represent a considerable self‐reported improvement . Assuming a standard deviation of 103.8, based on a former trial with IBS patients, a two‐sided, level 5% t test requires a total of 26 patients per study group in order to detect a respective group difference with a statistical power of 80%. To account for the potential loss of statistical power from the withdrawal of up to 10% of participants, the trial aimed to recruit a total of at least 58 patients.…”
Section: Methodsmentioning
confidence: 99%
“…It consists of three single questions that allow three different answers and a 100-point VAS on which 0 reflects the worst and 100 the best possible condition. All questionnaires have been used in German language before [26, 27]. In addition, stool frequency was quantified before and at the end of the study.…”
Section: Methodsmentioning
confidence: 99%
“…Using this definition, 57.9% of patients responded to treatment with humic acids and 36.8% of patients responded to treatment with placebo. Other studies using the same definition for a response have reported responses to treatment in between 43.9% and 81% of patients, and responses to placebo in between 18.9% and 46% of patients [50][51][52].…”
Section: Discussionmentioning
confidence: 96%